2008
DOI: 10.1021/ja801594s
|View full text |Cite
|
Sign up to set email alerts
|

Antiparallel Arrangement of the Helices of Vesicle-Bound α-Synuclein

Abstract: alpha-Synuclein (alphaS) is the main component of Lewy bodies from Parkinson's disease. That alphaS binds to membranes is known, but the conformation it adopts is still unclear. Pulsed EPR on doubly spin-labeled variants of alphaS sheds light on the most likely structure. For alphaS bound to vesicles large enough to accommodate also the extended conformation, an antiparallel helix conformation is found. This suggests that the bent structure shown is the preferred conformation of alphaS on membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
118
1
3

Year Published

2009
2009
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(128 citation statements)
references
References 30 publications
6
118
1
3
Order By: Relevance
“…However, the conformation of AS on lipid membranes is still a subject of discussion. Some EPR reports suggest a broken-helix conformation (40,41) similar to that of the micelle-bound protein (42), whereas others show an extended ␣-helix for residues 9 -90 (43,44), a finding that is also supported by single molecule FRET measurements (45,46).…”
mentioning
confidence: 86%
“…However, the conformation of AS on lipid membranes is still a subject of discussion. Some EPR reports suggest a broken-helix conformation (40,41) similar to that of the micelle-bound protein (42), whereas others show an extended ␣-helix for residues 9 -90 (43,44), a finding that is also supported by single molecule FRET measurements (45,46).…”
mentioning
confidence: 86%
“…1A) (20,21,26). EPR analyses of ␣-synuclein derivatives bound to small unilamellar lipid vesicles (SUVs) have provided evidence for an elongated helical structure devoid of significant tertiary packing (28), or suggested a broken helical structure more recently (29,30). To relate these reported micelle-and vesicle-bound experimentally-observed structures, we previously carried out a detailed ensemble thermodynamic characterization of the SDS-induced folding of ␣-synuclein in broad ranges of SDS concentration, temperature, and pH, using CD spectroscopy, providing evidence for an inherently multistate ␣-synuclein folding (22).…”
mentioning
confidence: 99%
“…Several ensemble biophysical methods including NMR (20,21,26,27), EPR (28)(29)(30), CD (21,22,31,32) and fluorescence spectroscopy (33,34) have provided valuable insights into the structural features of disordered and folded ␣-synuclein. In the context of membrane-binding, solution NMR studies performed in the presence of SDS spherical micelles demonstrated that micelle-bound ␣-synuclein adopts a broken ␣-helix structure, which consists of a pair of curved antiparallel helices connected by a well-ordered extended linker, and followed by a short extended region and a predominantly unstructured mobile tail (Fig.…”
mentioning
confidence: 99%
“…Nevertheless, studies using smaller diameter spheroidal micelles, but also certain vesicle preparations (e.g. containing exclusively 1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-(1Ј-rac-glycerol) (POPG) lipids), showed that the elongated helix can be broken, resulting in an antiparallel arrangement of two helices (21)(22)(23)(24)(25)(26)(27) or a mixture of elongated and broken helices (28). In addition, a distinct helix break can be avoided even on a micelle by rearranging the amphiphilic amino acid sequence (29).…”
mentioning
confidence: 99%
“…S5). This SUV type will bias ␣S toward antiparallel conformations (26), but because both ␣S(Cys 11 -Cys 81 ) and ␣S(Cys…”
mentioning
confidence: 99%